Community Empowerment With HR Management Training By Smart Indonesia Academy To Bank Sulutgo Malang - Tanti Widia Nurdiani (Joong-Ki : Jurnal Pengabdian Masyarakat, 2022)
Smart Indonesia Academy, as a management consulting firm, provides management training on overcoming obstacles in the digital era of Industrial Revolution 4.0, particularly in light of the disruption caused by the COVID-19 pandemic, which needs the Bank Sulutgo team to accomplish everything digitally. This type of training is an activity that promotes community empowerment. The goal of this study is to investigate the Smart Indonesia Academy program, which involves giving human resource management training to Bank Sulutgo Malang in the context of community empowerment. This study employs a qualitative approach combined with an analytical descriptive strategy. According to the study's findings, Smart Indonesia Academy conducted this community service project at the Bank Sulutgo Malang office on February 21, 2022, which was attended by the Bank Sulutgo Malang staff as part of their HR management training. To make sure that human resource training is done right, it follows a lot of rules. These rules help the Bank Sulutgo Malang team answer the Smart Indonesia Academy's 2W1H (Why, What, and How) questions.